2015
DOI: 10.1016/j.tips.2014.10.005
|View full text |Cite
|
Sign up to set email alerts
|

What would be the observable consequences if phospholipid bilayer diffusion of drugs into cells is negligible?

Abstract: For drug transport across (i.e., through) an intact biological membrane, two main routes are possible: drugs may cross (i) through the phospholipid bilayer portion of the membrane, and/or (ii) via proteinaceous pores or transporters. Perhaps surprisingly, there is in fact no direct scientific evidence that the first of these takes place at any significant rate because, in the experiments performed to date, it has neither been varied as an independent variable nor measured directly as a dependent variable. Usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 50 publications
(50 citation statements)
references
References 60 publications
3
47
0
Order By: Relevance
“…7b), and also rather hydrophobic; only two endogenites have a Tanimoto similarity exceeding 0.5, though its similarity to related drugs is indeed reasonably high. (The same phenomena attach to sepantronium bromide, a potent drug candidate for which significantly more than 99% of uptake flux into cells occurs via a single transporter (SLC35F2) [11], and for which any phospholipid bilayer transport is consequently negligible [10, 13, 17, 121]; data not shown. )…”
Section: Resultsmentioning
confidence: 83%
“…7b), and also rather hydrophobic; only two endogenites have a Tanimoto similarity exceeding 0.5, though its similarity to related drugs is indeed reasonably high. (The same phenomena attach to sepantronium bromide, a potent drug candidate for which significantly more than 99% of uptake flux into cells occurs via a single transporter (SLC35F2) [11], and for which any phospholipid bilayer transport is consequently negligible [10, 13, 17, 121]; data not shown. )…”
Section: Resultsmentioning
confidence: 83%
“…As assessed in that paper (César-Razquin et al 2015), solute carriers (SLCs (Hediger et al 2004)) or transporters are the most neglected group of genes in the human genome. Our own analyses also point up their major importance in flux control (Walter et al 1987), drug transport (Dobson et al 2009a; Dobson and Kell 2008; Kell 2013, 2015a, 2015b, 2016; Kell et al 2013, 2011; Kell and Oliver 2014; Lanthaler et al 2011; Mendes et al 2015; O’Hagan and Kell 2015a) and biotechnology (Kell et al 2015b). Thus we consider that, although challenging, compartment-based metabolomics, where such transporters are necessarily involved, is likely to become a substantial field of itself.…”
Section: Quo Vadis? How Will the Full Potential Of Metabolomics Be Rementioning
confidence: 60%
“…These studies showed that the major part of high molecular mass compounds was not absorbed by the gut, while possibly up to 30% of the ingested dose of low molecular mass compounds was absorbed. In experiments in vivo , a limited panel of studies showed that only 1%–3% of the ingested amounts of protein bound Amadori products were recovered in the urine, which indicated that there is very little if any intestinal transport for much of these compounds but possibly an absorption by diffusion [(Erbersdobler and Faist, ), see however a reflection suggesting that permeation always requires transporters (Kell, )], specific excretion in the gut lumen or degradation by the host metabolism.…”
Section: The Taming Of Fire and Its Consequencesmentioning
confidence: 99%